THE BENEFITS OF CONDUCTING AN INTERNAL AUDIT OF COST ACCOUNTING AND CALCULATION USING INTERNATIONAL STANDARDS AND PRINCIPLES (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article discusses the advantages of applying international standards, principles and methods in the process of conducting an internal audit of cost accounting and product costs. Scientific proposals and practical recommendations are given for improving the internal audit of cost accounting and calculating the cost of production in business entities.